Effect of Pelvic Radiation on Haematopoeitic and Gastrointestinal Syndromes: a Prospective & Observational Study - Sharmin, Shaila; Mostafa, Sk Golam; Islam, Md Moynul; Trina, Shamima Afroz; Sarkar, Anannya (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Radiotherapy may induce irreversible damage on healthy tissues surrounding the tumor. It has been reported that the majority of patients receiving pelvic radiation therapy show early or late tissue reactions of graded severity as radiotherapy affects not only the targeted tumor cells but also the surrounding healthy tissues. This prospective, observational study was conducted to observe the effects of pelvic radiation on haematopoeitic and gastrointestinal syndromes. It was done in Radiation Oncology department of National Institute of Cancer Research and Hospital, Dhaka between July 2011 to June 2012. The study participants were all patients getting pelvic radiation in the concerned department. A blood profile was done before radiotherapy. Clinical evaluation as per RTOG Guideline was done to access the gastrointestinal syndromes. Then, pelvic radiation was started and CBC was done and recorded weekly as well as gastrointestinal toxicity grading. Main outcome measures were hemoglobin, TC of WBC, nausea, vomiting, diarrhea. Before treatment the mean hemoglobin % was 11.0±1.1 mg/dl, during 4th week of treatment it 10.37±0.7 mg/dl.The mean TC of WBC was found 11107.4±13481.4 mm3, during 4th week of treatment the mean TC of WBC was found 7550.6±2514.6 mm3.Nausea and vomiting increased upto 3rd week but decline in subsequent follow-up. 42% patients had diarrhea during 2ndand 3rd week of treatment, 20.0% in 4thweek and only 2.0% found in 5th week. It can be said that hematopoetic and gastrointestinal syndromes are significantly correlated in patients undergoing pelvic radiation following 4th week of follow up reports. J Bangladesh Coll Phys Surg 2024; 42: 31-37